Você está na página 1de 3

∂z/∂x ∂z/∂y

z = x 3 + y 3 3axy

z = ln(x + x 2 + y 2 )

z = ln sen x + a

y

z = x y

y

x +

z =

y

x

z = x 2 y 2

z = arctg x

y

z = xye xy

z = x y

y

z =

x 1

y

z = e sen x

z =

x

x 2 + y 2

z = x y + 2 P (3, 2)

z = xy + x 2 P (2, 0)

w = x 3 y 4 z 5 P (0, 1, 1)

w =

xz

y + z P (1, 1, 1)

z =

tg 1 x P (1, 1)

y

w = ln(1 + e xyz ) P (2, 0, 1)

z = sen(x y) P (π/3, 4)

u =

x y 2 2 P (3, 1, 1, 2)

z + w

z =

1

x 2 + y 2 P (3, 4)

z = xy + x P (2, 1)

y

w = x yln(z) P (e, 2, e)

z = ln(x 2 + xy + y 2 )

x

∂z ∂x + y

y ∂z = 2

x

∂z

∂x =

z = xe y

∂z

∂y

z = x + y

x y

x ∂x ∂z + y

y ∂z = 0

z = x 2 + y 2

x

∂z ∂x + y

y ∂z = z

x w + y w + z w

∂x

∂y

∂z

x 2 + y 2 + z 2 x ∂w

∂x

1

+ y w + z w

∂y

y

∂z

∂z ∂x x

w = x 2 + yz

=

2w

w =

=

2w

y ∂z = 0

z = f (x 2 + y 2 ) f

f (x, y) = Ax 2 + 2Bxy + Cy 2

f (x, y) =

x

x 2 + y 2

f (x, y) = ln

y

x

z = ln(x 2 + y)

2 z ∂x 2

2 z ∂x∂y

2 z ∂y 2

f (x, y) =

x + y

x 2 + y 2

z = x y

z

∂x∂y =

2

2 z ∂y∂x

f (x, y)

f (x, y) =

= e x y 2 P (2, 2)

f (x, y) = x 2 y 2 P (2, 1)

f (x, y) = e xy P (2, 0)

cos(x/y) P (π, 4)

f (x, y) = x

x + y P (1, 1)

y

z = x 4 4xy 3 + 6y 2 2

S z =

xye (x 2 +y 2 )/2

z = 2x 2 + y 2

f (x, y) = xe xy (1, 0)

(1.1, 0.1) f (1.1, 0.1) = 0, 98542

(1, 1, 3)

(1, 02) 3 .(0, 97) 2

(4, 05) 2 + (2, 93) 2

f (x, y) = x 2 y df (1, 2)

z = x 3 + y 3 3xy

z

=

x 2 y 3

z = x 2 y 2 2

x 2 + y

z = yx y

z = ln(x 2 + y 2 )

z = x 2 e 3y x = 3.05 y = 0.02

g(s, t) = s 2 /t g(2.1, 1.9)

F (x, y, z) = x 2 + y + 2 + z 2 F (0.7, 2.6, 1.7)

u = xsen(x + y) x =

π

2 +

1

20 y =

π

1

2 30

l

a 4mm b 1mm dl

a

=

10cm

b

=

24cm

x ∂z = 3(x 2 ay)

 

y ∂z = 3(y 2 ax)

∂z

2y

∂z

∂x =

(x + y) 2

∂y =

y

∂z

1

∂z

x

 

∂z

y

∂y =

x

∂x =

x 2 y 2

∂y =

x 2 y 2

 
 

y

2

∂z

xy

∂z

1

∂z

(x 2 + y 2 ) 3/2

∂y =

(x 2 +

y 2 ) 3/2

∂x =

x 2 + y 2

∂y =

y

∂z

x

x 2 + y 2

∂z ∂y = x 1

e

sen(

y

x

∂z

x =

) cos

yx y1

y

x

∂y = x + a

∂z

y cotg x + a

y

2y

y ∂z = x y ln(x)

∂z

∂x = x 2

∂z

∂x =

∂z

∂x = − x 2 + y 2 ∂z ∂y = y y y 2
∂x = − x 2 + y 2
∂z
∂y =
y
y
y
2 e sen
x cos
∂x =
x
x
∂z
1
x + a
√ y cotg
∂x =
y

2x

(x + y) 2

y

x 2 + y 2 (x + x 2 + y 2 )

∂z

x = (xy 2 + y)e xy y = (x 2 y + x)e xy

∂z

∂z

y

∂z

1

∂x =

(x 1) 2

∂y =

x 1

1 π/24

1 1

4 2

0 0 0

3/125 4/125

1/2 1/4 1/4

1/2 1/2

2e e 2 2e

1/3 2/3 2/9 8/9

2 z

∂x 2

=

2(y x 2 )

(x 2 + y) 2

2

2x

∂x∂y = (x 2 + y) 2

2 z

∂y 2

=

1

(x 2 + y) 2

0 1 0 1/2 0

z = e 6 (x+4y)9e 6

z = 1 + 2y

z = 4x 2y 3

(1, 1) (0, 0) (1, 1)

z = x/2 y/2

16 2 = 4x + πy + 16

z = 0 S (0, 0) z = 1/e S (1, 1) (1, 1) z = 1/e

S (1, 1) 1, 1

z = 4x + 2y 3

L(1.1, 0.95) = 3.3 L(2, 3) = 11

 

L(x, y) = x + y L(1.1, 0.1) = 1

1, 00

4, 998

dz = 3(x 2 y)dx+3(y 2 x)dy

dz = 2xy 3 dx+3x 2 y 2 dy

dz = y 2 x y1 dx + x y (1 + ylnx)dy

dz =

2

x 2 + y 2 (xdx + ydy)

df = 4dx + dy

dz =

4xy y 2 ) 2 (ydx xdy)

(x 2 +

 

2s

s 2

8, 76

dg =

t dx

t 2 dt

g(2.1, 1.9) 2, 3

=

dz = 2xe 3y dx + 3x 2 e 3y dy

dF = xdx + ydy + zdz

z

=

+ z 2 F (0.9, 2.2, 1.9) 3.1

=

x 2 + y + 2

du = (sen(x + y) + xcos(x + y))dx + xcos(x + y)dy u π/120

dl = 0, 062cm l = 0, 065cm

=